Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Di Sumatera Barat Tahun 2015-2019 - Niva Yelfina; Marwan Marwan (Jurnal Ecogen, 2022)
The porpuse of this research is to know the effect of population growth, human development indeks (HDI) and poverty toward economics growth in West Sumatera with Fixed Effect Model (FEM) as selected model using panel data during the period 2015 until 2019. The technique of collecting data are documentation and library studies from relevant institutions. Independent variables of this research are Population Growth (X1), Human Development Indeks (X2) and Poverty (X3). Then the dependent variable is Economics Growth (Y). The research method are determination coeffisient test (R2), hypothesis test used T-test and F-test with 5 % significance level. The result of this research are : population growth has a positive significant effect on economics growth, human development indeks has a positive significant effect on economics growth, and poverty has a negative significant effect on economics growth. Then the simultaneously result is population growth, human development indeks, and poverty has an effect on economics growth in West Sumatera.Keywords : economics growth, population growth, human development indeks, poverty